REFERENDUM AS AN INSTRUMENT OF DEMOCRACY IN A STATE GOVERNED BY THE RULE OF LAW: AN ANALISYS THROUGH THE LENS OF THE ROMANIAN CONSTITUTIONAL COURT’S CASE-LAW - Bărbățeanu, Valentina (International Journal of Legal and Social Order, 2025)
The paper intends to highlight the importance of the referendum in a democratic State and to stress the need that its organization and conduct have to be in accordance with the standards required by a State governed by the rule of law. The role of the Constitutional Court will also be depicted and its case-law will be briefly presented in what concers the most relevant aspects of the referendum as an instrument used by the citizens in order to participate in the decision-making process at the State level.